Analisis Kualitas Air Situ Citayam dan Situ Pladen di Kota Depok Menggunakan Indeks Pencemar - Satria Mandala Widya Sakti; Diana Hendrawan; Rositayanti Hadisoebroto (Jurnal Lingkungan dan Kota, 2021)
The research objective is to determine the potential activities that cause pollution, to analyze the water quality and to determine the quality status of Citayam and Pladen lake. From the data ini 2017-2019, water quality of Citayam lake had pH ranging from 8.18 to 8.52, BOD ranging from 20.2-12.5 mg/L, COD ranging from 46.9-48.56 mg/L, DO ranging from 2.21 to 4.78 mg/L, Phosphate ranging from 0.0088-0.51 mg/L, Nitrate ranging from <0.1-2.55 mg/L, Fecal Coliform ranging from 79-160,000 MPN/100 ml, Total Coliform ranging from 240-300,000 MPN/100 ml, fatty oils ranging from <1,000-500 µg/liter, detergents ranging from <0.14-37.3 µg/liter. As for the water quality Pladen lake in 2017-2019, pH ranges from 7.17-9.00 mg/L, BOD ranges from 11.7-150 mg/L, COD ranges from 27.3-361.1 mg/L, DO ranges from 2 , 1-3.51 mg/L, Phosphate ranges from 0.25 to 0.95 mg/L, Nitrates ranges from 0.5-2.54 mg/L, Fecal Coliform, ranges from 210-220,000 MPN/100 ml, Total Coliform ranges 1,600-160,000 MPN/100 ml, oils and fats ranges from 300-2,000 µg/liter, detergents ranges from <0.014-70.3 µg/liter. The parameters which exceed the quality standard is caused by the activities around it. The value of the Citayam lake Pollutant Index in 2017 was 3,850, in 2018 was 3,763, in 2019 was 8,761. The quality status of Citayam Lake in 2018 is in the lightly polluted category, meanwhile, it is moderately polluted in 2017 and 2019. The Pladen lake Pollutant Index value was 7,888 in 2017, 6,948 in 2018, and 9,902 in 2019. The quality status of Pladen lake is moderate.